The first sample of spectroscopically confirmed ultra-compact massive galaxies in the Kilo Degree Survey. Issue 4 (20th September 2018) - Tortora, C; Napolitano, N R; Spavone, M; La Barbera, F; D'Ago, G; Spiniello, C; Kuijken, K H; Roy, N; Raj, M A; Cavuoti, S; Brescia, M; Longo, G; et al.
Abstract: We present results from an ongoing investigation using the Kilo Degree Survey (KiDS) on the VLT Survey Telescope (VST) to provide a census of ultra-compact massive galaxies (UCMGs), defined as galaxies with stellar masses ${M_{\star }}\gt 8 × 10^{10} \, \rm { M_\odot}$ and effective radii ${R_{\rm e}}\lt 1.5\, \rm kpc$ . UCMGs, which are expected to have undergone very few merger events, provide a unique view on the accretion history of the most massive galaxies in the Universe. Over an effective sky area of nearly 330 deg 2, we select UCMG candidates from KiDS multicolour images, which provide high quality structural parameters, photometric redshifts, and stellar masses. Our sample of ∼1000 photometrically selected UCMGs at $z$ < 0.5 represents the largest sample of UCMG candidates assembled to date over the largest sky area. In this paper, we present the first effort to obtain their redshifts using different facilities, starting with first results for 28 candidates with redshifts $z$ < 0.5, obtained at NTT and TNG telescopes. We confirmed, as bona fide UCMGs, 19 out of the 28 candidates with new redshifts. A further 46 UCMG candidates are confirmed with literature spectroscopic redshifts (35 at $z$ < 0.5), bringing the final cumulative sample of spectroscopically confirmed lower- z UCMGs to 54 galaxies, which is the largest sample at redshifts below 0.5. We use these spectroscopic redshifts to quantify systematic errors in our photometric selection, and use these to correct our UCMG number counts. We finally compare the results to independent data sets and simulations.